Diesel Engine Performance and Exhaust Emission Analysis Using Diesel-Organic Germanium Fuel Blend - Syafiq, Zulkifli; O., Fahmi; N., Syuhaida; Abdul Adam, Abdullah (2016)
The global diesel fuel stock has been decreasing due to its non-renewable source. Hence, many researchers have focused on an alternative fuel that can reduce the use of fossil fuel. Alternative fuels such as biodiesel, bio-alcohol and other biomass sources have been extensively research to find its potential to be used in internal combustion engines aimed at discovering alternative sources to fossil fuels. The advantage of using biodiesel is that is produces less greenhouse gases overall than fossil fuels when burn and less particulates such as soot and other fine particles. This experiment compared the performance of pure diesel (D), biodiesel (BD) and organic germanium-biodiesel blend (BG5) at five different speeds ranging from 1200 rpm to 2400 rpm. Results showed that BG5 shows a different combustion performance compared to BD. When compared to BD in terms of engine power, no significant changes observed at a low speed (1200 rpm). On the contrary, at higher speeds (1800 rpm and 2400 rpm), BG5 blend fuel showed increased engine power of 12.2 % and 9.2 %, respectively. Similarly, results on torque showed similar findings as engine power, whereby the improvement could be seen at higher speeds (1800 rpm and 2400 rpm) when torque increased by 7.3 % and 2.3 %, respectively. In addition, the emission results indicated that for all speeds, CO2, and NO had reduced at an average of 2.1 % and 177 %, respectively. Meanwhile, CO emission had slightly increased compared to BD at low speeds by 0.04 %. However, the amount of CO released had decreased at an average of 0.03 % as the engine speed increased. Finally, measurement of O2 shows an increment at 16.4 % at all speed range.